Implementasi Sapras untuk Mendukung Kenyamanan Belajar Siswa Sekolah Dasar - Nita Ariyani; Achadi Budi Santoso; Enung Hasanah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The availability of adequate educational facilities and infrastructure (sapras) is the main foundation for creating a conducive learning environment in elementary schools. However, the reality in the field often shows a significant disparity with the ideal conditions expected. This study aims to explore the implementation of sapras and its implications for student learning comfort. Through a qualitative research design, data was collected through participatory observation, document review, and in-depth interviews with 16 informants, including school principals, teachers, staff, and school committees. The data were analyzed thematically through coding, categorization, and validity testing using triangulation. The findings confirm that there is a gap in the quality of facilities, particularly in terms of furniture, ventilation, and supporting facilities, which directly impacts students' physical and psychological comfort. The analysis results show that the provision of adequate facilities has a significant positive impact: creating more active and enjoyable learning, deepening understanding of the material (cognitive aspect), and increasing student motivation and enthusiasm for learning (psychological aspect